A simple, efficient and accurate Bézier extraction based T-spline XIGA for crack simulations. (April 2017) - Singh, S.K.; Singh, I.V.; Mishra, B.K.; Bhardwaj, G.; Bui, T.Q.
Highlights: Bézier extraction based T-spline XIGA (BEBT-XIGA) is found quite suitable to solve crack problems. Results obtained by BEBT-XIGA are found in good agreement with NB-XIGA and analytical solutions. BEBT-XIGA with less number of control points provides better results as compared to NB-XIGA. BEBT-XIGA is found more efficient as compared to NB-XIGA. Bézier extraction provides an efficient way to implement T-splines into finite element code. Abstract: In the present work, a simple, efficient and accurate Bézier extraction based T-spline XIGA (BEBT-XIGA) has been proposed for the crack simulations. Bézier extraction maps T-spline basis functions over the element in the forms of Bernstein polynomial basis defined over the Bézier element. T-spline basis functions over the element can be written as linear combination of Bernstein polynomials basis. Bézier extraction approach generates an element extraction operator and Bézier element for fracture analysis. A crack is modelled in BEBT-XIGA through enrichment functions similar to XFEM. The values of stress intensity factors (SIFs) are computed using domain based interaction integral approach. Several crack problems have been solved by the proposed BEBT-XIGA approach.